Development of validation instruments for BIPA teaching material in Mindanao, Philippines - Yunia Tiara Riski; Nurul Istiq’faroh; Sukartiningsih, Wahyu; Neni Mariana; Ganes Gunansyah; Muhammad Nur Huda (Universitas Nahdlatul Ulama Surabaya, 2025)
This research aimed to develop validation instruments for Indonesian language for Foreign Speakers (BIPA) teaching materials based on the Pancasila Student Profile (P3) that is contextual and relevant for students of the Indonesian Basic Knowledge Course (KPDI) in Mindanao, Southern Philippines. KPDI is an initiative of the Indonesian Consulate General in Davao City as a form of Indonesian education service, which would serve as a bridge to formal education at the Indonesian School of Davao (SID). This research used a step of research and development (R&D) approach with a 4D model (define, design, develop, disseminate), which focuses on the develop step, specifically the development of instruments to test the validity, practicality, and effectiveness of teaching materials being developed. The instruments developed include validation questionnaires by experts in terms of material, language, media, and graphics; observation sheets; teacher and student response questionnaires; as well as reading comprehension tests, which are analyzed using the N-Gain test. It is hoped that the results of the instruments developed can become a reference in preparing BIPA teaching materials, which not only improve students' Indonesian language skills but also instill Indonesian national character values ​​through the Pancasila Student Profile approach.